The modern pattern of insect herbivory predates the advent of angiosperms by 60 My - Lifang Xiao; Liang Chen; Conrad C. Labandeira; Lauren Azevedo-Schmidt; Yongjie Wang; Dong Ren (Proceedings of the National Academy of Sciences, 2025)
Modern ecosystems display complex associations of plants–insects that underwent a long evolutionary process since the appearance of mid-Paleozoic vascular plants. Although several major hypotheses explain the evolution of these plant–insect associations, the initial pattern of modern insect herbivory is poorly understood. To understand the antiquity of modern patterns of terrestrial arthropod herbivory, functional feeding group–damage type (FFG-DT) data were used to analyze a 305 My interval from Late Pennsylvanian to present, in which 134 plant assemblages were used to assess turnover (replacement of some species by other species between sites) and nestedness (difference in composition when no species are replaced between sites) in pairwise comparisons of DTs. Results of beta diversity analyses indicate that the prototype pattern for modern insect herbivory was established on gymnosperm-dominated plant assemblages by late Middle Jurassic, antedating angiosperm dominance by 60 My. Turnover among plant groups and FFGs declined in earlier late Paleozoic, whereas during the later Cenozoic, nestedness generally increased. Insect feeding on gymnosperms showed one pattern of change with low turnover and high nestedness, whereas a bimodal pattern characterized angiosperms. Ferns and angiosperms exhibited less DT functional breadth (host-plant “specificity” by herbivores) than gymnosperms, reflecting major differences in links between insect herbivores and their host plants. This fundamental trophic shift is consistent with the Mid-Mesozoic Parasitoid Revolution, implying top–down control of herbivores by their consumers rather than bottom–up regulation of food sources that shaped the modern herbivory pattern. These findings provide a data-rich account of the ecological origins of modern herbivory.